Analisis Faktor Individu, Faktor Organisasi dan Kelelahan Kerja Terhadap Stres Kerja Pada Perawat (Studi di Ruang Rawat Inap Kelas III RSU dr. H. Koesnadi Kabupaten Bondowoso) (Analysis of Individual Factors, Organization Factor and Occupational Fatigue W - Ekin Akhsa Febriandini; Isa Ma`rufi; Ragil Ismi Hartanti (Pustaka Kesehatan, 2016)
Hospital is a health service place. The service claims can create some danger like work stress. Based on the preliminary studies that has been done at General Hospital dr.H Koesnadi, Bondowoso district , found that 67 % nurses experienced the occupational fatigue and work stress. The work stress is influenced by some factors like individual factors (gender, age, length of service and level of education), organization factor like work shift and occupational fatigue in the hospital's employee. Human resource has potential about the work stress of nurse in handly the patient directly. The purpose of this research is to analyze the relation between individual factors, organization factor and occupational fatigue in the work stress. The method that used in this research is analytical observation with the cross sectional design. The sampel of this research is 46 respondents that spread over 5 inpatient room 3rd grade.The result of this research showed that there was a significant relation between individual factors and work stress (p = 0,004), the relation between the organization factor and the work stress (p = 0,038). It is also known that there was a relation between occupational fatigue with the work stress (p = 0,047) Keywords: Individual Factors, Organization Factors, Occupatiunal Fatigue, Work Stress